Trends and Persistence in the Greenland Ice Sheet Mass - Guglielmo Maria Caporale; Luis Alberiko Gil-Alana; Laura Sauci (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines trends and persistence in the Greenland ice sheet mass by applying fractional integration methods to a dataset constructed by Mankoff et al. (2020) on ice discharge for seven different regions of Greenland. The adopted empirical framework encompasses a wide range of stochastic processes and is informative about their dynamic and long-run properties. The main finding is that significant changes have occurred in the behaviour of the series of interest in recent years; more specifically, although a deterministic trend is not present, ice discharge in the various regions of Greenland has become a non-stationary, explosive process, with shocks having permanent effects. It appears that, as a result of global warming, the ice mass loss in Greenland has already reached a tipping point and become an irreversible process.
Keywords: C22; Q54; 330; Greenland ice sheet mass; long memory; fractional integration; persistence; trends